Fatty Acid Biosynthesis: Chain‐Length Regulation and Control. (27th June 2019) - Heil, Christina S.; Wehrheim, S. Sophia; Paithankar, Karthik S.; Grininger, Martin
Abstract: De novo biosynthesis of fatty acids is an iterative process requiring strict regulation of the lengths of the produced fatty acids. In this review, we focus on the factors determining chain lengths in fatty acid biosynthesis. In a nutshell, the process of chain‐length regulation can be understood as the output of a chain‐elongating C−C bond forming reaction competing with a terminating fatty acid release function. At the end of each cycle in the iterative process, the synthesizing enzymes need to "decide" whether the growing chain is to be elongated through another cycle or released as the "mature" fatty acid. Recent research has shed light on the factors determining fatty acid chain length and has also achieved control over chain length for the production of the technologically interesting short‐chain (C4 –C8 ) and medium‐chain (C10 –C14 ) fatty acids. Abstract : Molecular rulers : Fatty acid biosynthesis is an iterative process requiring strict chain‐length regulation. Key players in chain‐length regulation are the three enzymes—acyltransferases (ATs), ketosynthases (KSs), and thioesterases (TEs)—that determine chain elongation or termination. Bioengineering of fatty acid synthases (FASs) can overwrite chain‐length control to generate platform chemicals for biofuel production.